Urban transition governance in practice: exploring how European cities govern local transitions to achieve climate neutrality - Doci, Gabriella; Dorst, Hade; Hillen, Stanislas; Tjokrodikromo, Tess (Frontiers in Sustainable Cities, 2025)
The European Union's “100 Climate Neutral and Smart Cities Mission” launched in 2021, urges European cities to collaborate with local stakeholders to develop transition plans (Climate City Contracts) aimed at achieving climate neutrality by 2030. This initiative represents the largest urban transition experiment to date, offering valuable lessons for future urban transformations. This article assesses cities' initial efforts to implement the transition governance model through the lens of the analytical framework that focuses on four key functions drawn from the transition management literature: coordination, co-creation, anchoring, and governance learning. Using a mixed-methods approach, the study examines the extent to which these functions have been operationalized, and the early experiences cities have had in applying them. This study presents findings on how cities govern transitions and underscores the difficulties of coordination and management when delegated to municipalities instead of practitioners or researchers. The Cities Mission provides a unique opportunity to study multiple cross-sectoral urban transition experiments, as each city customizes its approach to local conditions. To enhance urban climate transitions, it is imperative to examine transition governance within its inherent context, enabling the insights gained to offer substantial and thorough guidance to municipalities and significantly advance the practical implementation of transition management theory. A comparative analysis of these evolving transition scenarios deepens our understanding of how cities operationalize transition management and the complexities involved in long-term urban sustainability transformations.